2012
DOI: 10.1001/archoto.2011.1176
|View full text |Cite
|
Sign up to set email alerts
|

Brachytherapy-Mediated Bone Damage in a Rat Model Investigating Maxillary Osteoradionecrosis

Abstract: Similar to the mandible, the maxilla is susceptible to radiogenic bone injury as demonstrated by the significant decrease in bone volume of the radiated dental extraction socket. Despite radiologic similarities to mandibular ORN in the rat model, the maxilla demonstrated a more benign clinical course with a complete absence of bone exposure. Differences in the maxillary bone and microenvironment of the maxilla compared with the mandible may explain the subclinical response to radiation and lower incidence of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
(28 reference statements)
1
6
0
Order By: Relevance
“…Although severity of osteonecrosis can be assessed in histological sections based on loss of viable osteocytes 11, 17 , the earliest histological criteria for definitive diagnosis of osteonecrosis are still debatable due to its multifactorial etiology from radiation, drugs, alcohol, infection and trauma 6, 24, 27, 37 . This pilot study involves a limited number of experimental animals but it is consistent with a previous ORN study that showed that limited sample size can still be used to define skeletal outcomes of radiation 38 . Despite the limited sample size, the outcomes suggest apparent site-disparity in the onset and cellular features of ORN in the jaws relative to long bones with mandible being more susceptible to ORN than tibia.…”
Section: Discussionsupporting
confidence: 74%
“…Although severity of osteonecrosis can be assessed in histological sections based on loss of viable osteocytes 11, 17 , the earliest histological criteria for definitive diagnosis of osteonecrosis are still debatable due to its multifactorial etiology from radiation, drugs, alcohol, infection and trauma 6, 24, 27, 37 . This pilot study involves a limited number of experimental animals but it is consistent with a previous ORN study that showed that limited sample size can still be used to define skeletal outcomes of radiation 38 . Despite the limited sample size, the outcomes suggest apparent site-disparity in the onset and cellular features of ORN in the jaws relative to long bones with mandible being more susceptible to ORN than tibia.…”
Section: Discussionsupporting
confidence: 74%
“…Six studies applied in vivo micro-CT, performed in the maxilla [6], [15], [20], [21] and in the condyle [10], [22]. The scanning device which was most often used was the μCT 40 (Scanco Medical, Brüttisellen, Switzerland) [9], [11], [13], [14], [19], [23], [24], [25], [26], [27], [28], [29], [30], [31], followed by the Skyscan apparatus (Skyscan, Aartselaar, Belgium) [3], [4], [8], [20], [21], [32], [33], [34], [35]. The results of the quantitative analysis are presented in Table 2, Table 3, Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the most frequently analysed regions of interest were the alveolar bone surrounding the first molar tooth and the interradicular septal bone. The effect of drug interventions on the maxillar bone was investigated in 4 studies [3], [8], [16], [23], with extraction sockets as region of interest for assessing the drug-induced bone response. Only 1 study [9] focused on the effect of mechanical loading on the alveolar bone.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations